VD_FINDINFO Décision / 2013 / 483 vom 30. Mai 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, PROPORTIONNALITÉ, PRINCIPE DE LA CÉLÉRITÉ, RISQUE DE RÉCIDIVE | 212 al. 3 CPP (CH), 221 CPP (CH), 5 CPP (CH)